Aktualność antropologii św. Jana Pawła II ukazanej w przemówieniach podczas pielgrzymki do Polski w 1979 roku - Przygoda, Wiesław (Społeczeństwo, 2022)
One of the main topics that John Paul II discussed during his pilgrimage to Poland in 1979 was the topic of the man. The Polish pope knew perfectly the anthropological errors propagated in Poland by people of the communist system until the end of the Second World War. Moreover, prior to his visit to Poland, on 4 March 1979 he announced his first encyclical: Redemptor hominis. It should be of no surprise then that John Paul II, in the words addressed to Poles, often discussed the following subject: who is a man, where does he come from, what is their destination, and how can we assess a man? The pope did not focus, however, or even did not put the main highlight on criticism of the communist anthropology, but he tried to draw the attention of his countrymen to the positive lecture on the Christian studies on human beings. The goal of this article is to present, in a systematic way, the main anthropological theses in John Paul II’s speeches during his stay in Poland in 1979 and to indicate how those words are still meaningful, 40 years later. The article is of review and it is mainly based on John Paul II’s teachings given on 2-10 June 1979 in Poland, which have sometimes been supplemented with other speeches, in particular from the encyclical titled Redemptor hominis.